2015
DOI: 10.2105/ajph.2015.302552
|View full text |Cite
|
Sign up to set email alerts
|

The Health at Every Size Paradigm and Obesity: Missing Empirical Evidence May Help Push the Reframing Obesity Debate Forward

Abstract: A Health at Every Size (HAES) approach has been proposed to address weight bias and stigma in individuals living with obesity, and more recently articulated as a promising public health approach beyond the prevailing focus on weight status as a health outcome. The purpose of this article is to examine our understanding of HAES within the context of public health approaches to obesity, and to present strengths and limitations of the available evidence. Advancing our understanding of HAES from a public health pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 46 publications
1
89
0
7
Order By: Relevance
“…T h e r e h a s b e e n a r e c e n t c a l l f o r m o r e e m p i r i c a l r e search on weight-neutral programs for 589 health promotion among those with high BMI (Penney & Kirk, 2015). The current study has 590 responded to this call, and addresses a gap in the literature by focusing on the mechanisms that 591 may enhance or undermine the success of weight-neutral programs.…”
Section: Conclusion 588mentioning
confidence: 99%
“…T h e r e h a s b e e n a r e c e n t c a l l f o r m o r e e m p i r i c a l r e search on weight-neutral programs for 589 health promotion among those with high BMI (Penney & Kirk, 2015). The current study has 590 responded to this call, and addresses a gap in the literature by focusing on the mechanisms that 591 may enhance or undermine the success of weight-neutral programs.…”
Section: Conclusion 588mentioning
confidence: 99%
“…Prevention efforts should also include programs to reduce financial stress in families and programs aimed at teaching children on how to cope with stressors in their environment (86). It has been suggested that overweight and obesity reductions may accrue if the prevention focus is shifted, more broadly, to promoting healthy lifestyles and healthy environments and beyond the focus on individual children's body weight as the outcome (136). The opportunities for early health promotion require attention simultaneously to many levels (30), suggesting the need to address the individual, family, and physical environment, the social environment, and social policy.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…The medicalization of obesity has reified the problem as its own distinct ailment and 'cause' of other chronic conditions-rather than as a symptom of unhealthy behavioral patterns (Oliver 2006:8-11). New approaches to health management such as the 'Health at Every Size' movement have argued for a 'weight neutral' approach rather than health improvement through weight reduction-a strategy that has demonstrated limited effectiveness (Penney and Kirk 2015). The Ministry of Health, Labor, and Welfare's approach is in some ways compatible with this idea.…”
Section: Resultsmentioning
confidence: 99%